Grammatical comprehension deficits in non-fluent/agrammatic primary progressive aphasia. Issue 3 (13th September 2013) - Charles, Dorothy; Olm, Christopher; Powers, John; Ash, Sharon; Irwin, David J; McMillan, Corey T; Rascovsky, Katya; Grossman, Murray
Abstract : Importance: Grammatical comprehension difficulty is an essential supporting feature of the non-fluent/agrammatic variant of primary progressive aphasia (naPPA), but well-controlled clinical measures of grammatical comprehension are unavailable. Objective: To develop a measure of grammatical comprehension and examine this comparatively in PPA variants and behavioural-variant frontotemporal degeneration (bvFTD) and to assess the neuroanatomic basis for these deficits with volumetric grey matter atrophy and whole-brain fractional anisotropy (FA) in white matter tracts. Design: Case–control study. Setting: Academic medical centre. Participants: 39 patients with variants of PPA (naPPA=12, lvPPA=15 and svPPA=12), 27 bvFTD patients without aphasia and 12 healthy controls. Main outcome measure: Grammatical comprehension accuracy. Results: Patients with naPPA had selective difficulty understanding cleft sentence structures, while all PPA variants and patients with bvFTD were impaired with sentences containing a centre-embedded subordinate clause. Patients with bvFTD were also impaired understanding sentences involving short-term memory. Linear regressions related grammatical comprehension difficulty in naPPA to left anterior-superior temporal atrophy and reduced FA in corpus callosum and inferior frontal-occipital fasciculus. Difficulty with centre-embedded sentences in other PPA variants was related to other brain regions. Conclusions and relevance: These findings emphasise a distinct grammatical comprehension deficit in naPPA and associate this with interruption of a frontal-temporal neural network.